2021
DOI: 10.1186/s13052-021-01028-1
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset sepsis risk calculator: a review of its effectiveness and comparative study with our evidence-based local guidelines

Abstract: Background According to most early-onset sepsis (EOS) management guidelines, approximately 10% of the total neonatal population are exposed to antibiotics in the first postnatal days with subsequent increase of neonatal and pediatric comorbidities. A review of literature demonstrates the effectiveness of EOS calculator in reducing antibiotic overtreatment and NICU admission among neonates ≥34 weeks’ gestational age (GA); however, some missed cases of culture-positive EOS have also been describe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Puopolo and Mukhopadhyay conducted a study of 15,433 infants born at 22 to 28 weeks’ gestation in Neonatal Research Network centers from 2006 to 2014, those born by cesarean delivery with membrane rupture at delivery and absence of clinical chorioamnionitis were significantly less likely to have confirmed EOS [ 2 ]. Additionally, the neonatal EOS calculator is a clinical risk stratification tool increasingly used to guide the use of empirical antibiotics for newborns [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Puopolo and Mukhopadhyay conducted a study of 15,433 infants born at 22 to 28 weeks’ gestation in Neonatal Research Network centers from 2006 to 2014, those born by cesarean delivery with membrane rupture at delivery and absence of clinical chorioamnionitis were significantly less likely to have confirmed EOS [ 2 ]. Additionally, the neonatal EOS calculator is a clinical risk stratification tool increasingly used to guide the use of empirical antibiotics for newborns [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…chorioamnionitis were significantly less likely to have confirmed EOS [2]. Additionally, the neonatal EOS calculator is a clinical risk stratification tool increasingly used to guide the use of empirical antibiotics for newborns [28]. In recent years, numerous studies have demonstrated that unnecessary or long-term use of antibiotics can increase the risk of adverse clinical outcomes in premature infants, and prolonged use of broad-spectrum antibiotics can cause strong selective pressure on microorganisms, which will in turn induce drug-resistance [29].…”
Section: Discussionmentioning
confidence: 99%
“…Limiting the clinical examination only to newborns with EOS risk factors can lead to missed diagnoses in newborns with no perinatal warnings [ 38 , 39 , 40 ]. We report the case of one patient of the P2 population, with no pre- or perinatal risk factors, who developed a severe form of GBS sepsis that led to his death.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to prevent neonatal sepsis, its early diagnosis, and timely treatment are essential to reduce its incidence, mortality, and sepsis-related complications [ 3 , 4 ]. However, clinical presentation may be nonspecific, reliable early markers of sepsis are currently unavailable, and risk factors have insufficient predictive value [ 5 , 6 ]. In preterm very-low-birth-weight (VLBW) infants, both the incidence of sepsis and the associated risks of mortality or complications are higher than in full-term infants [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%